The Role of Organizational Culture and Organizational Commitments in Determining the Quality of Work-Life and Employee Performance at PT Carrefour Supermarket Denpasar - Dewa Ayu Tita Permata Tabita; I Nengah Suardhika; Putu Kepramareni (Global Academia Publisher, 2021)
This study aims to determine the effect of organizational culture and organizational commitment on employee performance, with work-life as a mediating variable. This study uses an explanatory research design. The population of this study was 76 permanent employees at PT Carrefour Supermarket Denpasar. The analytical tool was descriptive analysis. This study used SEM analysis with the SmartPLS 3.0 program. The findings indicate that organizational culture (X1) has a positive and significant effect on the quality of work-life and employee performance. Organizational commitment (X2) has a positive and significant effect on the quality of work-life and employee performance. The quality of work-life (Y1) has a positive and significant effect on employee performance.